Projeto escola de tempo integral no estado do Pará : um estudo a partir da Escola Estadual Maria Conôr em Castanhal/PA - SANTOS, Lucilene do Socorro da Costa (2018)
Full-time education has been a topic under discussion in Brazil since the first decades of the twentieth century, in the State of Pará, in 2012, the respective Integral School project was implemented with the aim of improving the education offered by the State. This Course Completion Work analyzes the development of the full-time school project in the State of Pará, based on the Maria Conôr State School located in the municipality of Castanhal / PA, the project was implemented in 2013, attending the classes of the third, fourth and fifth year of primary education with students between the ages of 9 and 14 The study focused on the analysis of the project, its organization and functioning, the limits presented by it, as well as its contribution to the teaching process of students. This is a qualitative approach in which a field research was carried out, in which a structured interview was conducted with two teachers and the director of the teaching unit, documentary analysis of the resolution on the fulltime school project of the State of Pará and bibliographical readings of authors such as: ARROYO (1988); (PARO, 1988) and CAVALIERE (2002), among others, who discuss the theme in question. The study revealed that the full-time school project of the State of Pará implemented in the researched school does not have the necessary support on the part of the Secretary of Education, because the proposal announced at the beginning of the implementation of the aforementioned project was not materialized, a fact that harms the operation of the project.The conception of full time education of the subjects who work in the project is the conception of assistance. the school has been able to consolidate partnerships that contribute significantly to the actions that the school does and that, despite the lack of support, training for the professionals involved in the project, the school maintains its functioning by executing the activities developed in the project in accordance with the reality of the school unit because it understands that it is a project that contributes significantly to the process of teaching learning, which facilitates student development.